Analysis of the Traditionalist and Modernist Characteristics in the Interpretation of Al-Muawwidzatain in Al-Qaul Al-Bayan and Al-Burhan - Akbar Ramadhan; Andri; Muhammad Irfan (TOFEDU: The Future of Education Journal, 2025)
This research is motivated by the writer’s interest in the various styles of exegesis (tafsir) that have developed, and the tendency for each style to have its own characteristics. Among the styles of exegesis, there are those with linguistic, philosophical, Sufi, legal, scientific, literary, and social characteristics. In its development, not only these styles exist, but in West Sumatra, the polemic between traditionalist and modernist groups has also influenced the interpretation styles of scholars in the context of certain verses. Traditionalists are a group that emphasizes the importance of tradition in understanding everything, including in the study of exegesis. Meanwhile, the modernist group emphasizes modern characteristics in responding to everything, including their study of the Quranic verses (tafsir). This research uses a qualitative method with a literature study approach (Library Research). The primary sources in this research are the exegesis books al-Qaul al-Bayan and al-Burhan. Secondary sources include books, articles, and scholarly writings related to the research. The analysis in this study uses the characteristics of traditionalism and modernism. The findings show that the traditionalist characteristics are evident in al-Qaul al-Bayan in five ways: referring to the four founders of the schools of thought, particularly Imam Shafi’i, i.e., the Quran, Hadith, Ijma’ (consensus), and Qiyas (analogy); the knowledge is reinforced in classical Islamic texts (kitab kuning); it is influenced by the religious teachings of Sufism, particularly Imam Ghazali; it justifies additional practices; and it emphasizes the importance of tariqa (spiritual paths). The modernist characteristics are evident in al-Burhan in three ways: its ideology refers to the Quran and Sunnah, it uses a rational approach to oppose bid’ah (innovation) and khurafat (superstition), and it focuses more on the enhancement of faith.